Hybrid molecules of estrone: new compounds with potential antibacterial, antifungal, and antiproliferative activities - Adamec, Jan; Beckert, R; Weiss, D; Klimešová, Věra; Waisser, Karel; Mollmann, U; Kaustová, Jarmila; Buchta, Vladimír (Bioorganic & medicinal chemistry, 2007)
New hybrid molecules of estrone were synthesized as compounds indicating promising biological activity (antibacterial, antimycobacterial, antifungal, and antiproliferative). The prepared molecules contained various heterocyclic units (pyridine, benzylsulfanyl derivatives of pyridine or derivatives of tetrazole) linked to estrone by n-heptyl bridges. The compounds with charge on molecule (the hybrid pyridinium or benzylsulfanylpyridinium salts) exhibited significant biological activity (antibacterial, antimycobacterial, antifungal, and antiproliferative). On the other hand, the compounds not in the form of salts (omega-(1-phenyl-5-tetrazolylthio)heptylethers of estrone) were inactive. The antimycobacterial activities of three different series of tetrazole derivatives (i.e., the hybrid molecules with estrone, tetrazole-5-thiols, and 5-benzylsulfanyl-1-phenyltetrazoles) with the same substituents on phenyl ring were compared. Amongst them, the 5-benzylsulfanyl-1-phenyltetrazoles were the most potent.
Keywords: financování organizované; proliferace buněk; Antifungal Agents; antituberkulotika; mikrobiální testy citlivosti; Cell Line, Tumor; houby; Estrone; indikátory a reagencie; chromatografie na tenké vrstvě; lidé; Antineoplastic Agents; protinádorové látky; Anti-Bacterial Agents; Heterocyclic Compounds; Indicators and Reagents; heterocyklické sloučeniny; Spectrophotometry, Infrared; Financing, Organized; Fungi; magnetická rezonanční spektroskopie; Microbial Sensitivity Tests; Bacteria; spektrofotometrie infračervená; Cell Proliferation; Antitubercular Agents; Cell Survival; estron; Magnetic Resonance Spectroscopy; Chromatography, Thin Layer; viabilita buněk; antibakteriální látky; antifungální látky; nádorové buněčné linie; Humans